Holistic Education Management and Students’ Adaptive Abilities: A Case Study at State Senior High School 10 Medan - Diana Diana; Mesiono Mesiono; Achyar Zein (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores how holistic education management contributes to students’ adaptive abilities in academic and social contexts at State Senior High School 10 Medan. In the face of 21st-century challenges, adaptability has become a critical skill, and holistic education offers a promising framework. Using a qualitative case study design, data were collected through interviews, observations, and document analysis involving school leaders, teachers, students, and parents. Thematic analysis was employed to interpret patterns related to curriculum, pedagogy, collaboration, and school culture. Findings reveal four key components that support student adaptability. First, the integration of academic, character, social, and spiritual elements in the curriculum enhances students’ academic and social resilience. Second, Project-Based Learning fosters critical thinking, creativity, and teamwork. Third, collaboration among schools, families, and communities strengthens social support and broadens learning experiences. Fourth, an inclusive school culture promotes empathy, tolerance, and flexible social skills. These practices significantly contribute to students’ adaptive capacities but face constraints such as limited teacher competence and insufficient policy support. The study confirms that adaptability emerges from the integration of holistic curriculum, innovative learning, collaborative partnerships, and inclusive culture. It highlights the need for coherent education policies and sustained teacher development to scale such practices.